What we don't know can hurt us: Nonresponse bias assessment in birth defects research. Issue 7 (14th July 2015) - Strassle, Paula D.; Cassell, Cynthia H.; Shapira, Stuart K.; Tinker, Sarah C.; Meyer, Robert E.; Grosse, Scott D.
Abstract : BACKGROUND: Nonresponse bias assessment is an important and underutilized tool in survey research to assess potential bias due to incomplete participation. This study illustrates a nonresponse bias sensitivity assessment using a survey on perceived barriers to care for children with orofacial clefts in North Carolina. METHODS: Children born in North Carolina between 2001 and 2004 with an orofacial cleft were eligible for inclusion. Vital statistics data, including maternal and child characteristics, were available on all eligible subjects. Missing 'responses' from nonparticipants were imputed using assumptions based on the distribution of responses, survey method (mail or phone), and participant maternal demographics. RESULTS: Overall, 245 of 475 subjects (51.6%) responded to either a mail or phone survey. Cost as a barrier to care was reported by 25.0% of participants. When stratified by survey type, 28.3% of mail respondents and 17.2% of phone respondents reported cost as a barrier. Under various assumptions, the bias‐adjusted estimated prevalence of cost as barrier to care ranged from 16.1% to 30.0%. Maternal age, education, race, and marital status at time of birth were not associated with subjects reporting cost as a barrier. CONCLUSION: As survey response rates continue to decline, the importance of assessing the potential impact of nonresponse bias has become more critical. Birth defects research is particularly conducive to nonresponse bias analysis, especially when birth defect registries and birth certificate records are used. Future birth defect studies which use population‐based surveillance data and have incomplete participation could benefit from this type of nonresponse bias assessment. Birth Defects Research (Part A) 103:603–609, 2015. © 2015 Wiley Periodicals, Inc.